Development of a genetic risk score to predict the risk of hypertension in European adolescents from the HELENA study - Pérez-Gimeno, Gloria; Seral-Cortes, Miguel; Sabroso-Lasa, Sergio; Esteban, Luis Mariano; Lurbe, Empar; Béghin, Laurent; Gottrand, Frederic; Meirhaeghe, Aline; Muntaner, Manon; Kafatos, Anthony; Molnár, Dénes; Leclercq, Catherine; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction From genome wide association study (GWAS) a large number of single nucleotide polymorphisms (SNPs) have previously been associated with blood pressure (BP) levels. A combination of SNPs, forming a genetic risk score (GRS) could be considered as a useful genetic tool to identify individuals at risk of developing hypertension from early stages in life. Therefore, the aim of our study was to build a GRS being able to predict the genetic predisposition to hypertension (HTN) in European adolescents. Methods Data were extracted from the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) cross-sectional study. A total of 869 adolescents (53% female), aged 12.5–17.5, with complete genetic and BP information were included. The sample was divided into altered (≥130 mmHg for systolic and/or ≥80 mmHg for diastolic) or normal BP. Based on the literature, a total of 1.534 SNPs from 57 candidate genes related with BP were selected from the HELENA GWAS database. Results From 1,534 SNPs available, An initial screening of SNPs univariately associated with HTN (p < 0.10) was established, to finally obtain a number of 16 SNPs significantly associated with HTN (p < 0.05) in the multivariate model. The unweighted GRS (uGRS) and weighted GRS (wGRS) were estimated. To validate the GRSs, the area under the curve (AUC) was explored using ten-fold internal cross-validation for uGRS (0.802) and wGRS (0.777). Further covariates of interest were added to the analyses, obtaining a higher predictive ability (AUC values of uGRS: 0.879; wGRS: 0.881 for BMI z-score). Furthermore, the differences between AUCs obtained with and without the addition of covariates were statistically significant (p < 0.05). Conclusions Both GRSs, the uGRS and wGRS, could be useful to evaluate the predisposition to hypertension in European adolescents.